High-blackness high-gloss carbon pigment black master batch special for polycarbonate as well as preparation and application of high-blackness high-gloss carbon pigment black master batch
By modifying the carbon pigment and using maleic anhydride grafted polyolefin wax as a dispersant, a high-black and high-gloss carbon pigment black masterbatch was prepared, which solved the negative impact of traditional carbon black additives on polycarbonate, and achieved the improvement of high blackness and high gloss and appearance quality of polycarbonate products.
Patent Information
- Application Number
- CN202411581022.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-28
AI Technical Summary
Traditional carbon black additives have a negative impact on the mechanical properties and thermal stability of polycarbonate, and it is easy to lead to poor uniformity of masterbatches during the preparation process, making it difficult to achieve high blackness and high glossiness of polycarbonate products. At the same time, there are appearance defects such as silver wires and white spots, resulting in high product scrapping rate.
By modifying the carbon pigment, the agglomeration between the pigments is reduced, and its compatibility and dispersion with polycarbonate resin is improved. Maleic anhydride grafted polyolefin wax is used as a dispersant to improve the gloss and dispersion of the masterbatches, and black carbon pigment black masterbatches with high blackness and high gloss are prepared.
The high blackness and high gloss properties of polycarbonate are achieved, while maintaining the appearance of the product without flaws and does not affect its other properties, such as impact strength and melt index, reducing the scrap rate of the product.
Smart Images

Figure BDA0005123099430000091 
Figure HDA0005123099440000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of plastic coloring, and in particular relates to a black masterbatch of carbon pigment specially used for polycarbonate with high blackness and high gloss, and preparation and application thereof. Background Art
[0002] Polycarbonate (PC) is an amorphous thermoplastic resin with excellent comprehensive properties, including excellent electrical insulation, elongation, transparency, dimensional stability, high impact strength and chemical resistance, high heat resistance and cold resistance, etc. It is increasingly used in the fields of automobiles, home appliances, building materials, etc. In recent years, the demand for high-gloss piano black spray-free products in the automobile, home appliances, and building materials industries has gradually increased.
[0003] Traditional carbon black additives may have a negative impact on the mechanical properties and thermal stability of PC plastics. Secondly, carbon black additives are prone to accumulation and agglomeration during the preparation process, resulting in poor uniformity of the masterbatch. In order to improve the defects of carbon black masterbatch, the method of adding organic black (dye black, oil black, solvent violet, etc.) is currently used to achieve high blackness and high gloss of PC products, such as patent application CN117467262A uses dye red, dye yellow, dye green, and dye blue color matching; patent application CN114806123A uses organic red, yellow, and blue powders or is configured with oil black powder; patent application CN114276666A uses aniline black; patent application CN113999510A uses anthraquinone-based black dye; patent application CN109401298A dye black; patent application CN104017347A uses perylene organic pigments to prepare high gloss and high blackness PC composite materials. However, the cost of organic black is much higher than that of carbon black. More importantly, many organic blacks such as aniline black are alkaline, while the ester group of polycarbonate is extremely sensitive to alkali, which easily leads to degradation of polycarbonate during extrusion and injection molding, resulting in silver streaks and white spots on the surface of the product. For piano black products with extremely high requirements for appearance, the product is very likely to have a very high scrap rate. Therefore, it is particularly important to prepare a black masterbatch for high-gloss piano black polycarbonate to achieve the high blackness and high gloss characteristics of polycarbonate while maintaining its flawless appearance and no negative impact on other properties. Summary of the invention
[0004] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a high-blackness and high-gloss carbon pigment black masterbatch for polycarbonate. Polycarbonate is used as a carrier resin to modify the carbon pigment, reduce the agglomeration between the pigments, and improve its compatibility and dispersibility with the polycarbonate resin; at the same time, maleic anhydride grafted polyolefin wax is used as a dispersant to improve the gloss and dispersibility of the masterbatch; and a well-dispersed high-blackness and high-gloss carbon pigment black masterbatch is prepared. The carbon pigment black masterbatch has high gloss, high blackness, good dilution and dispersibility when used for polycarbonate coloring.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned high-blackness and high-gloss carbon pigment black masterbatch for polycarbonate.
[0006] Another object of the present invention is to provide the use of the above-mentioned high-blackness and high-gloss carbon pigment black masterbatch for polycarbonate in the coloring of polycarbonate.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A high-blackness and high-gloss carbon pigment black masterbatch for polycarbonate, comprising the following components in parts by weight:
[0009] 40-70 parts of polycarbonate resin, 24-50 parts of modified carbon pigment, and 1-5 parts of maleic anhydride grafted polyolefin wax.
[0010] Preferably, the carbon pigment black masterbatch comprises the following components in parts by weight:
[0011] 44.5-70 parts of polycarbonate resin, 24.5-50 parts of modified carbon pigment, and 1-5 parts of maleic anhydride grafted polyolefin wax.
[0012] Preferably, the modified carbon pigment is obtained by the following method: firstly, the carbon pigment is subjected to heating and oxidation modification, and then subjected to a grafting reaction with a long-chain alkyl compound to obtain the modified carbon pigment.
[0013] More preferably, the carbon pigment is at least one of carbon black and carbon nanotubes.
[0014] The carbon black has a particle size of 10 to 20 nm and a specific surface area of 180 to 550 m 2 / g furnace carbon black, more preferably Olilong's 50L, Cabot's BLACK 900, PvBlack X90 of Xinjiang Dexin New Materials Co., Ltd. and ZY-1 of Qujing Zhongyi Fine Chemical Co., Ltd.
[0015] The carbon nanotubes are multi-walled carbon nanotubes with a diameter of 5 to 30 nm and a length of 1 to 30 um; more preferably, NANOCYL TM At least one of NC7000, GT-300 of Dazhan Nanomaterials Co., Ltd. and FT-9000 of Jiangsu Tiannai Technology Co., Ltd.
[0016] More preferably, the oxidant used for the oxidative modification is hydrogen peroxide; the mass ratio of the carbon pigment to the oxidant is 100:1.5-3; and more preferably 100:2.
[0017] More preferably, the temperature of the heating oxidation modification is 60 to 80° C., and the time is 12 to 24 hours.
[0018] More preferably, the mass ratio of the carbon pigment to the long-chain alkyl compound is 100:0.5-1.5; further preferably, it is 100:1.
[0019] More preferably, the long-chain alkyl compound is octadecylsulfonyl chloride.
[0020] More preferably, the grafting reaction temperature is 80-110° C., and the time is 0.5-1.5 h; more preferably 1 h.
[0021] Preferably, the polycarbonate resin is a bisphenol A type polycarbonate resin having a melt flow rate of 5 to 20 g / 10 min (300° C., 1.2 kg); more preferably, the polycarbonate resin of Wanhua Company 2100, 2200, Covestro LED2045, Teijin's At least one of L-1225L.
[0022] Preferably, the maleic anhydride grafted polyolefin wax is an olefin polymer having an anhydride group with a number average molecular weight of 2000 to 10000, wherein the acid value is 40 to 150 mgKOH / g; more preferably, HI-WAX manufactured by Mitsui Chemicals TM 1105A, LUCANT TM A-5515, manufactured by Clariant Chemicals PE MA 4351 and DIACARNA manufactured by Mitsubishi Chemical Corporation TM At least one of 30M.
[0023] The addition of maleic anhydride grafted polyolefin wax improves the dispersion stability and compatibility of carbon pigment in PC resin, thereby improving the gloss of masterbatch and products.
[0024] Preferably, the high-blackness and high-gloss carbon pigment black masterbatch for polycarbonate comprises 0 to 2 parts of antioxidant.
[0025] More preferably, the antioxidant is 0.2 to 0.5 parts.
[0026] More preferably, the antioxidant is at least one of a phenolic antioxidant and a phosphite antioxidant; more preferably, BASF 1010, 1076, 1098, BASF 168 and At least one of the P-EPQs.
[0027] The method for preparing the above-mentioned high-blackness and high-gloss carbon pigment black masterbatch for polycarbonate comprises the following steps:
[0028] (1) kneading the polycarbonate resin in an internal mixer until it is completely plasticized;
[0029] (2) adding the modified carbon pigment, maleic anhydride grafted polyolefin wax, or the modified carbon pigment, maleic anhydride grafted polyolefin wax, and an antioxidant into the internal mixer of step (1), and kneading until all the materials are transformed into a melt mass with a smooth surface, thereby obtaining a mixed material;
[0030] (3) The mixed product is extruded and granulated by a twin-screw extruder to obtain black masterbatch.
[0031] Preferably, the temperatures of the banburying in steps (1) and (2) are both 210-250°C.
[0032] Preferably, the top bolt pressure of the internal mixer in steps (1) and (2) is 0.4-0.7 MPa, and more preferably 0.6 MPa.
[0033] Preferably, the temperature of the twin-screw extruder in step (3) is set to: 230-250°C, double-cone feeding section 150-170°C, head temperature 245-255°C; screw speed 300-500rpm.
[0034] The above-mentioned high-blackness and high-gloss carbon pigment black masterbatch for polycarbonate is used in the coloring of polycarbonate.
[0035] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0036] (1) The addition of maleic anhydride grafted polyolefin wax reduces the viscosity of the system, improves the dispersion stability and compatibility of the modified carbon pigment in the PC resin, and thus improves the gloss of the masterbatch and the product;
[0037] (2) By modifying the surface of the carbon pigment, the agglomeration force between the pigment particles is reduced, and the combination of the carbon pigment and the polycarbonate macromolecular chain is increased, which is conducive to the transmission and dispersion of stress, and improves the dispersion morphology and dispersion stability of the carbon pigment in the carrier resin matrix, so that the carbon pigment black masterbatch will not have a negative impact on other properties of the product such as impact strength and melt index when coloring polycarbonate;
[0038] (3) The obtained black masterbatch does not contain alkaline groups. While giving the polycarbonate a high blackness and high gloss color, it will not cause defects such as silver streaks and white spots on the surface of the product, thereby reducing the scrap rate of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a physical picture of the sample of Example 1. DETAILED DESCRIPTION
[0040] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0041] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0042] Example 1
[0043] (1) 100 kg of carbon black PvBlack X90 was added to a stirrer with a heating device, 2 kg of hydrogen peroxide was added dropwise while stirring, and the mixture was heated to 80° C., kept warm for 12 h under stirring, and then 1 kg of octadecylsulfonyl chloride was added, and the mixture was heated to 80° C. and stirred for 1 h to obtain a modified carbon pigment;
[0044] (2) 53.5 kg of polycarbonate resin 2100 is added to the internal mixer, and the temperature is turned on to reach 220℃. The internal mixer is started, and the upper bolt pressure is controlled at 0.6MPa. After the resin is completely plasticized, 43kg PvBlack X90 modified carbon black and 3kg maleic anhydride grafted polyolefin wax DIACARNA are added. TM 30M and 0.5kg antioxidant At 1010, the internal mixer was restarted, and the upper push bolt pressure was controlled at 0.6 MPa. The internal mixing was continued until all the materials became a melt mass with a smooth surface. The materials were added into the hopper of the double-cone feeder. The temperature of the double-cone feeding section was set to 165°C, the temperature of each section of the twin-screw extruder was set to 240°C, the head temperature was 245°C, and the screw speed was 425 rpm. The materials were then pelletized by water ring, dried, sieved, and homogenized to form black masterbatch.
[0045] Example 2
[0046] (1) 100 kg of carbon black 50L, add into a stirrer with a heating device, add 2kg of hydrogen peroxide dropwise while stirring, heat to 70°C, keep warm for 20h under stirring, then add 1kg of octadecylsulfonyl chloride, heat to 100°C and stir for 1h to obtain a modified carbon pigment;
[0047] (2) 44.5 kg of polycarbonate resin Add L-1225L to the internal mixer, turn on the heating to make the temperature reach 220℃, start the internal mixer, control the pressure of the upper push bolt at 0.4MPa, and add 50kg 50L modified carbon black, 5kg maleic anhydride grafted polyolefin wax PE MA 4351, 0.2kg antioxidant 1076 and 0.3kg antioxidant 168. Restart the internal mixer, control the upper push bolt pressure at 0.4 MPa, and continue to mix until all the materials become a melt mass with a smooth surface. Then add the materials into the hopper of the double-cone feeder, set the temperature of the double-cone feeding section to 170°C, set the temperature of each section of the twin-screw extruder to 250°C, the head temperature to 255°C, the screw speed to 300rpm, and then cut into pellets by water ring, dry, screen, and homogenize to finally form black masterbatch.
[0048] Example 3
[0049] (1) 70 kg of carbon black BLACK 900, 30kg multi-walled carbon nanotubes NANOCYL TM NC7000 was added to a stirrer with a heating device, and 2 kg of hydrogen peroxide was added dropwise while stirring, and the mixture was heated to 75°C. The mixture was kept warm for 24 hours while stirring, and then 1 kg of octadecylsulfonyl chloride was added, and the mixture was heated to 90°C and stirred for 1 hour to obtain a modified carbon pigment.
[0050] (2) 65.7 kg of polycarbonate resin LED2045 is added to the internal mixer, and the temperature is turned on to reach 220℃. The internal mixer is started, and the upper bolt pressure is controlled at 0.5MPa. After the resin is completely plasticized, 30kg of modified carbon pigment and 4kg of maleic anhydride grafted polyolefin wax LUCANT are added. TM A-5515, 0.2kg antioxidant 1076 and 0.1kg antioxidant P-EPQ, then start the internal mixer, control the upper bolt pressure at 0.5MPa, continue to mix until all the materials become a melt mass with a smooth surface, add the materials into the hopper of the double cone feeder, set the temperature of the double cone feeding section to 160℃, set the temperature of each section of the twin screw extruder to 230℃, the head temperature to 235℃, the screw speed to 500rpm, and then water ring pelletizing, drying, screening, homogenization to finally form black masterbatch.
[0051] Example 4
[0052] (1) 15kg of carbon black ZY-1, 75kg of carbon black BLACK 900, 10kg of multi-walled carbon nanotubes FT-9000 are added to a stirrer with a heating device, 2kg of hydrogen peroxide is added dropwise while stirring, heated to 70°C, kept warm for 24h under stirring, and then 1kg of octadecylsulfonyl chloride is added, heated to 90°C and stirred for 1h to obtain a modified carbon pigment;
[0053] (2) 63.5 kg of polycarbonate resin 2200 is added to the internal mixer, and the temperature is turned on to reach 220℃. The internal mixer is started, and the upper bolt pressure is controlled at 0.7MPa. After the resin is completely plasticized, 35kg of modified carbon pigment and 0.5kg of maleic anhydride grafted polyolefin wax are added. PE MA 4351; 0.5kg maleic anhydride grafted polyolefin wax DIACARNA TM 30M, 0.1kg antioxidant 1098 and 0.1kg antioxidant 168. Restart the internal mixer, control the upper push bolt pressure at 0.7 MPa, and continue to mix until all the materials become a melt mass with a smooth surface. Then add the materials into the hopper of the double-cone feeder, set the temperature of the double-cone feeding section to 160°C, set the temperature of each section of the twin-screw extruder to 235°C, the head temperature to 240°C, the screw speed to 450rpm, and then cut into pellets by water ring, dry, screen, and homogenize to finally form black masterbatch.
[0054] Comparative Example 1
[0055] 53.5kg polycarbonate resin 2100 was added to the internal mixer, and the temperature was turned on to reach 220℃. The internal mixer was started, and the upper bolt pressure was controlled at 0.6MPa. After the resin was completely plasticized, 43kg PvBlack X90 carbon black and 3kg maleic anhydride grafted polyolefin wax DIACARNA were added. TM 30M and 0.5kg antioxidant At 1010, the internal mixer was restarted, and the upper push bolt pressure was controlled at 0.6 MPa. The internal mixing was continued until all the materials became a melt mass with a smooth surface. The materials were added into the hopper of the double-cone feeder. The temperature of the double-cone feeding section was set to 165°C, the temperature of each section of the twin-screw extruder was set to 240°C, the head temperature was 245°C, and the screw speed was 425 rpm. The materials were then pelletized by water ring, dried, sieved, and homogenized to form black masterbatch.
[0056] Comparative Example 2
[0057] 53.5kg polycarbonate resin 2100 is added to the internal mixer, and the temperature is turned on to reach 220℃. The internal mixer is started, and the upper bolt pressure is controlled at 0.6MPa. After the resin is completely plasticized, 43kg PvBlack X90 carbon black, 3kg PETS wax and 0.5kg antioxidant are added. At 1010, the internal mixer was restarted, and the upper push bolt pressure was controlled at 0.6 MPa. The internal mixing was continued until all the materials became a melt mass with a smooth surface. The materials were added into the hopper of the double-cone feeder. The temperature of the double-cone feeding section was set to 165°C, the temperature of each section of the twin-screw extruder was set to 240°C, the head temperature was 245°C, and the screw speed was 425 rpm. The materials were then pelletized by water ring, dried, sieved, and homogenized to form black masterbatch.
[0058] Comparative Example 3
[0059] (1) 100 kg of carbon black 50L, add into a stirrer with a heating device, add 2kg of hydrogen peroxide dropwise while stirring, heat to 70°C, keep warm for 20h under stirring, then add 1kg of octadecylsulfonyl chloride, heat to 100°C and stir for 1h to obtain a modified carbon pigment;
[0060] (2) 40 kg of polycarbonate resin Add L-1225L to the internal mixer, turn on the heating to make the temperature reach 220℃, start the internal mixer, control the upper push bolt pressure at 0.4MPa, and add 54.5kg after the resin is completely plasticized. 50L modified carbon black, 5kg maleic anhydride grafted polyolefin wax PE MA4351, 0.2kg antioxidant 1076 and 0.3kg antioxidant 168. Restart the internal mixer, control the upper push bolt pressure at 0.4 MPa, and continue to mix until all the materials become a melt mass with a smooth surface. Then add the materials into the hopper of the double-cone feeder, set the temperature of the double-cone feeding section to 170°C, set the temperature of each section of the twin-screw extruder to 250°C, the head temperature to 255°C, the screw speed to 300rpm, and then cut into pellets by water ring, dry, screen, and homogenize to finally form black masterbatch.
[0061] Example 5
[0062] (1) 100 kg of carbon black 50L, add into a stirrer with a heating device, add 2kg of hydrogen peroxide dropwise while stirring, heat to 70°C, keep warm for 20h under stirring, then add 1kg of octadecylsulfonyl chloride, heat to 100°C and stir for 1h to obtain a modified carbon pigment;
[0063] (2) 70 kg of polycarbonate resin Add L-1225L to the internal mixer, turn on the heating to make the temperature reach 220℃, start the internal mixer, control the pressure of the upper push bolt at 0.4MPa, and add 24.5kg after the resin is completely plasticized. 50L modified carbon black, 5kg maleic anhydride grafted polyolefin wax PE MA4351, 0.2kg antioxidant 1076 and 0.3kg antioxidant 168. Restart the internal mixer, control the upper push bolt pressure at 0.4 MPa, and continue to mix until all the materials become a melt mass with a smooth surface. Then add the materials into the hopper of the double-cone feeder, set the temperature of the double-cone feeding section to 170°C, set the temperature of each section of the twin-screw extruder to 250°C, the head temperature to 255°C, the screw speed to 300rpm, and then cut into pellets by water ring, dry, screen, and homogenize to finally form black masterbatch.
[0064] Performance Testing:
[0065] Surface gloss and hue test
[0066] The black masterbatch prepared in Examples 1-4 and Comparative Example 1 was weighed and added to bisphenol A polycarbonate resin PC110 in an amount of 2wt%. After drying in a blast oven at 80°C for 4 hours, a standard sample and a color plate of 90mm*50mm*1mm were respectively injection molded by a plastic injection molding machine at an injection molding temperature of 280°C. The sample and the color plate were placed at a relative humidity of 50% and 23°C for at least 24 hours before performance testing. The specific test method and conditions are as follows:
[0067] 1. For L value test, use a 90mm*50mm*1mm color plate and Konica Minolta Spectrophotometer CM-700D to measure, and calculate the Lab value according to CIE1976 standard; L value indicates the depth of the material's black value. The lower the L value, the higher the black value; the smaller the b value, the bluer the hue and the darker the visual color.
[0068] 2. Gloss test, using a 90mm*50mm*1mm color plate, tested according to ISO 2813-2014 standard, 60° angle;
[0069] The lower the L value, the greater the glossiness (60°), indicating a higher degree of high gloss black.
[0070] 3. Impact strength retention rate test, using impact specimens, according to the national standard GB / T 1843-2008. Impact retention rate = impact strength after adding masterbatch / impact strength of pure PC110 × 100%.
[0071] 4. Melt index: break the color plate of 90mm*50mm*1mm and test it according to GB / T 3682.1-2018. The test conditions are 300℃ and 1.2kg.
[0072] Table 1 Performance comparison of each sample
[0073]
[0074] From Example 1 and Comparative Examples 1 and 2, it can be seen that the blackness and glossiness of the example are significantly higher than those of the comparative examples, and the example has little effect on the melt index and impact strength of the colored resin.
[0075] From Example 2 and Comparative Example 3, it can be seen that the amount of carbon black added in the example is too much, and the blackness, glossiness and impact retention rate are significantly reduced.
[0076] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A black masterbatch of carbon pigment for polycarbonate, characterized in that: By weight, it includes the following components: 40-70 parts of polycarbonate resin, 24-50 parts of modified carbon pigment, 1-5 parts of maleic anhydride grafted polyolefin wax; The modified carbon pigment is obtained by the following method: firstly, the carbon pigment is subjected to heating and oxidation modification, and then a grafting reaction is carried out with a long-chain alkyl compound to obtain the modified carbon pigment.
2. The carbon pigment black masterbatch for polycarbonate according to claim 1, characterized in that: By weight, it includes the following components: 44.5-70 parts of polycarbonate resin, 24.5-50 parts of modified carbon pigment, and 1-5 parts of maleic anhydride grafted polyolefin wax.
3. The carbon pigment black masterbatch for polycarbonate according to claim 1 or 2, characterized in that: The carbon pigment is at least one of carbon black and carbon nanotubes; The carbon black has a particle size of 10 to 20 nm and a specific surface area of 180 to 550 m 2 / g furnace carbon black; The carbon nanotubes are multi-walled carbon nanotubes with a diameter of 5 to 30 nm and a length of 1 to 30 um; The oxidant used in the oxidation modification is hydrogen peroxide; the mass ratio of the carbon pigment to the oxidant is 100:1.5-3; The mass ratio of the carbon pigment to the long-chain alkyl compound is 100:0.5-1.5; The long-chain alkyl compound is octadecylsulfonyl chloride; The temperature of the heating oxidation modification is 60 to 80°C and the time is 12 to 24 hours; The grafting reaction temperature is 80-110° C. and the time is 0.5-1.5 h.
4. The carbon pigment black masterbatch for polycarbonate according to claim 3, characterized in that: The carbon black is from Orion 50L, Cabot's BLACK 900, PvBlack X90 of Xinjiang Dexin New Materials Co., Ltd. and ZY-1 of Qujing Zhongyi Fine Chemical Co., Ltd.; The carbon nanotubes are NANOCYL TM At least one of NC7000, GT-300 of Dazhan Nanomaterial Co., Ltd. and FT-9000 of Jiangsu Tiannai Technology Co., Ltd.; The mass ratio of the carbon pigment to the oxidant is 100:2; The mass ratio of the carbon pigment to the long-chain alkyl compound is 100:
1.
5. The carbon pigment black masterbatch for polycarbonate according to claim 1 or 2, characterized in that: The maleic anhydride grafted polyolefin wax is an olefin polymer with an anhydride group and a number average molecular weight of 2000 to 10000, wherein the acid value is 40 to 150 mgKOH / g; The polycarbonate resin is a bisphenol A type polycarbonate resin having a melt flow rate of 5 to 20 g / 10 min at 300° C. and 1.2 kg.
6. The carbon pigment black masterbatch for polycarbonate according to claim 1 or 2, characterized in that: The maleic anhydride grafted polyolefin wax is HI-WAX manufactured by Mitsui Chemicals TM 1105A, LUCANT TM A-5515, manufactured by Clariant Chemicals PE MA 4351 and DIACARNA manufactured by Mitsubishi Chemical Corporation TM At least one of 30M; The polycarbonate resin is from Wanhua 2100, 2200, Covestro LED2045, Teijin's At least one of L-1225L.
7. The carbon pigment black masterbatch for polycarbonate according to claim 1 or 2, characterized in that: Including 0-2 parts of antioxidants; The antioxidant is at least one of a phenolic antioxidant and a phosphite antioxidant.
8. The carbon pigment black masterbatch for polycarbonate according to claim 7, characterized in that: Including 0.2-0.5 parts of antioxidant; The antioxidant was obtained from BASF 1010, 1076, 1098, BASF 168 and At least one of the P-EPQs.
9. The method for preparing a black masterbatch of carbon pigment for polycarbonate according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) kneading the polycarbonate resin in an internal mixer until it is completely plasticized; (2) adding the modified carbon pigment, maleic anhydride grafted polyolefin wax, or the modified carbon pigment, maleic anhydride grafted polyolefin wax, and an antioxidant into the internal mixer of step (1), and kneading until all the materials are transformed into a melt mass with a smooth surface, thereby obtaining a mixed material; (3) extruding the mixed material through a twin-screw extruder to obtain black masterbatch; The temperatures of the banburying in steps (1) and (2) are both 210-250° C.; The top bolt pressure of the internal mixer in steps (1) and (2) is 0.4-0.7 MPa; The temperature of the twin-screw extruder in step (3) is set to: 230-250° C., double-cone feeding section 150-170° C., die head temperature 245-255° C.; screw speed 300-500 rpm.
10. Use of the carbon pigment black masterbatch for polycarbonate according to any one of claims 1 to 8 in coloring polycarbonate.
Citation Information
Patent Citations
Polycarbonate-organosiloxane copolymer material capable of selectively transmitting near-infrared rays
CN104017347A
High-gloss piano black polyamide (PA) / polycarbonate (PC) alloy resin composition and preparation method thereof
CN109401298A
Polycarbonate resin composition and molded article comprising composition
CN113999510A
High-gloss high-surface-hardness polycarbonate composite material and preparation method thereof
CN114276666A
High-weather-resistance black PC resin composition as well as preparation method and application thereof
CN114806123A